MASA KERAJAAN TURKI UTSMANI SERTA FAKTOR KEMAJUAN DAN KEMUNDURAN - Muhammad Basri; Putri Puspita Hasri, Najwa Mahfudza, Fadiza Syafira Nasution (CV. Adiba Aisha Amira, 2023)
After the fall of the Abbasid dynasty, Islamic political power gradually began to lag behind. Some colonies sought their own independence in the form of small kingdoms. This condition certainly worsened the political power of Islam. This situation improved after the emergence of three great empires, namely the Ottoman empire in Turkey, the Mongol empire in India, and the Safavid kingdom in Persia. In historical records the Ottoman Empire is the first kingdom that has survived the longest, compared to two other major empires, namely the Mongol kingdom in India, and the Safavid kingdom in Persia, established in 1282-1929 AD. This kingdom came from the descendants of Uthman Ibn Sauji Ibn Arthogol Ibn Sulayman Shah Ibn Kia Alp. The establishment of this kingdom was on the initiative of the Turks from the Oghuz tribe, a Nomanic tribe in Asia Minor who inhabited the Mongol region and the northern area of China.Many advances made by the Ottoman Empire, both in the fields of culture, politics, military, and governance.